DESIGNING MADING ONLINE AT AMIK WAHANA MANDIRI, SOUTH TANGERANG - Rustam Effendi; Yasin Efendi (LPPM Unbaja, 2022)
Mading in general contains positive and informative things so that it can be an up to date, cheap, and creative communication medium. In terms of campus information, Mading can be conveyed news about the progress of the campus, both in the academic side of students and teaching lecturers as well as campus facilities and infrastructure. Inseparable from that, Mading Kampus can function as a campus promotion medium. However, with the development of the technological age that is increasingly practical in sharing information, Mading's role on campus is less interested by students because it is less interesting and less practical. In terms of work and achievements, Mading will accommodate the creativity of students who are very diverse in the form of ideas, ideas, thoughts, imagination, art, existing creative power. There needs to be a place to channel this creativity, therefore it is necessary to form an Online Mading at the dynamic AMIK Wahana Mandiri South Tangerang Campus by utilizing advanced PHP-based web technology. Keywords : Mading, Online, Web, PHP, MySQL, Technology, Information